A History of the Resilience of Black Girls. Issue 2 (1st July 2019) - Cook, Courtney
Abstract : Nazera Sadiq Wright. 2016. Black Girlhood in the Nineteenth Century. Urbana, University of Illinois Press. Black girls have a history of resilience. Nazera Sadiq Wright, in Black Girlhood in the Nineteenth Century (2016), analyzes accounts of the experiences of black girls from what she refers to as "youthful" girlhood to the conscious or "prematurely knowing" (44) age of 18. Setting out to recover overlooked accounts of black girlhood during the nineteenth century, a tumultuous epoch of transition for the black community, Wright uses contemporaneous literary and visual texts such as black newspapers, novels, poetry, and journals to reconstruct this lost narrative. By engaging in a close reading of these texts, in which black people, emerging from slavery, communicated with each other about personal and community goals, Wright examines the ways in which the instruction of black girls operated in between the lines of literature to convey codes of conduct to the black community. She argues that with the emergence of literature written by and for black women, the role of the black girl morphed from docile homemaker to resilient heroine for herself and her people. In discussing this more complex role, Wright does not deny that black girls were vulnerable to multiple forms of violence and hurt, but does point to a more nuanced experience. Black Girlhood in the Nineteenth Century is an intervention into the African American literary canon, filling in many of the gaps in the lost history of black girlhood, making it an essential text for those "who care" (22) about black girls as they engage in the process of rewriting and redeeming the narratives of an often-forgotten population.